Development of Arduino UNO-based Heat Practicum Tool with LM35 Sensor to Improve Student Graphic Interpretation - Mufid Eska Nurcahya; Sarwi Sarwi; Teguh Darsono (Universitas Negeri Semarang, 2025)
Technology is the result of the process of scientific development. 21st century technology has developed rapidly in the scope of education. High-level thinking is an important competency for students in the 21st century. For this reason, learning planning is needed that is able to improve high-level thinking competencies, especially in terms of student interpretation. Many practical lessons at SMA N 1 Balapulang are still not technology-based. This research aims to produce a practical tool based on Arduino UNO to improve graphic interpretation for high school students. This type of research is Research and Development (R & D) and uses a research model, namely ADDIE (Analysis, Design, Development, Implementation, Evaluation). Based on validation by tool experts, it was found that the practical tool media developed received a score of 92.5% in the very good category. The characteristics of the media developed are the Arduino UNO microcontroller with an LM35 sensor to read the temperature of the liquid being measured, the interface of the Arduino UNO is PLX-DAQ software so that it is stored in MS Excel, there is a LKPD developed to make it easier for students during practicum. The results of improving student graphic interpretation seen from the pre-test and post-test obtained an average score from 57.11% to 89.61%. The N-Gain value obtained was 0.72, where there was an increase in graphic interpretation for students in the high category. The results of the analysis of heat change calculations proportional to temperature changes can improve student interpretation of graphs.